Integrasi Tasawuf Dalam Logoterapi Sebagai Psikoterapi Santri Gangguan Jiwa Di Pp. Al-Syifa - Tasmuji .; Ahmad Khoirudin (Program Studi Tasawuf dan Psikoterapi, 2022)
The purpose of this study was to reveal the dimensions of Sufism in psychotherapy for people with mental disorders with the logotherapy method applied by psychotherapists in PP. Al-Syifa Ngawi. Logotherapy based on the search for self meaning is a therapy based on spirituality. The research method used is qualitative, the approach is descriptive analysis. From it, it can be seen that the psychotherapy model applied in PP. Al-Syifa Ngawi there are two of the three logotherapy techniques initiated by Viktor E. Frankl. The first is a dereflection technique where the psychotherapist provides positive activities according to the potential of students to divert them from negative symptoms. This technique integrates Sufism through takhalli and tahalli approaches. Secondly, spiritual guidance, this technique is very thick with the method in Sufism, where students are guided in knowing God again. Starting from learning prayer as the implementation of repentance, to being introduced to prayer, recitation and ruqyah as the implementation of dhikr in the field of Sufism.